INCREASING THE CAPACITY OF GAMPONG'S BUSINESS ENTITY (BUMG) IN AN EFFORT TO IMPROVE COMMUNITY WELFARE IN LANGSA CITY - Junita, Afrah; Andiny, Puty; Meutia, Tuti; Ellidar, Ellidar (CV. Radja Publika, 2022)
BUMG is one of the important considerations for channeling village community initiatives in developing village potential, managing and utilizing the potential of village natural resources, optimizing human resources (village residents) in their management, and the existence of capital participation from the village government in the form of financing and gampong wealth that submitted to be managed as part of BUMG. Through the development of gampong potentials accompanied by community participation in managing BUMG, it will encourage the village economy and create village economic independence. However, ironically, of the 66 BUMGs, only 30 are active and the rest are in suspended animation. According to the Head of BUMDes, the Gampong Community Empowerment Agency (BPMG) of Langsa City, the BUMDes have no creative ideas, so they do not have market competitiveness, and the weak resources that master technology, so they cannot connect the products produced by BUMG with the market by using technology. The results showed that Langsa City BUMG is in the first quadrant, namely the Strategy Quadrant for Supporting Aggressive Strategy where this quadrant is a very profitable situation because it is supported by strengths and opportunities so that it can take advantage of existing opportunities. The strategy taken is to support an aggressive growth policy (growth oriented strategy). Weak resources that master technology so that they cannot connect the products produced by BUMG with the market by utilizing technology. The results showed that Langsa City BUMG is in the first quadrant, namely the Strategy Quadrant for Supporting Aggressive Strategy where this quadrant is a very profitable situation because it is supported by strengths and opportunities so that it can take advantage of existing opportunities. The strategy taken is to support an aggressive growth policy (growth oriented strategy). Weak resources that master technology so that they cannot connect the products produced by BUMG with the market by utilizing technology. The results showed that Langsa City BUMG is in the first quadrant, namely the Strategy Quadrant for Supporting Aggressive Strategy where this quadrant is a very profitable situation because it is supported by strengths and opportunities so that it can take advantage of existing opportunities. The strategy taken is to support an aggressive growth policy (growth oriented strategy). The results showed that Langsa City BUMG is in the first quadrant, namely the Strategy Quadrant for Supporting Aggressive Strategy where this quadrant is a very profitable situation because it is supported by strengths and opportunities so that it can take advantage of existing opportunities. The strategy taken is to support an aggressive growth policy (growth oriented strategy). The results showed that Langsa City BUMG is in the first quadrant, namely the Strategy Quadrant for Supporting Aggressive Strategy where this quadrant is a very profitable situation because it is supported by strengths and opportunities so that it can take advantage of existing opportunities. The strategy taken is to support an aggressive growth policy (growth oriented strategy).